Necesidad de codificar en el código del trabajo del Ecuador el contrato., “Teletrabajo” en el ordenamiento laboral acorde con las modernas técnicas de la información introducidas en nuevas tecnologías - HERRERA DÍAZ, PATRICIA SORAYA (2015)
The current time marked by the undeniable phenomenon of the globalization that has had its most important handle in the technology of the communication by means of the use of tools of easy access like the internet, challenges to the science from the Right to reforms its old juridical positions around diverse thematic, one of them, the labor one. The modern techniques of the information introduced in great measure to productive activities have allowed the benefit of certain labor services outside of the managerial facilities. This new work form is the one that has been denominated as "telework", the same one that is assimilated to what the doctrinal currents settle down as work modality to home. Nevertheless this modern artificial figure has its own ones and characteristic matters that you/they emphasize the necessity of its regulation inside the legal-labor mark of our country. Since the call "society of the information" it is an undeniable reality, to the one that a number every growing time of Ecuadorian you leave included, partly for the normal process of the globalization, to which the inhabitants of our country are not other people's and on the other hand for the migratory process that has Spain like one of the destination countries preferred by the linguistic identity, is necessary to highlight that this European country is counted among the pioneers in the regulation of this interesting phenomenon of the "telework". The presence of the teleworker is not indispensable in the physical home of the company, that which in way some means the non-supervision or control of the carried out works, the one that stays with immediately in spite of the distance. Another of the advantages of the telework is also presented in the ecological environment, because it impacts in the paper saving, space in the office and other expenses. In such a way that the productivity is also increased without a strong investment on the part of the company. Inside the social field, the juridical regulation of the "telework" it bears better labor conditions as much for the teleworker as for the employer. The first one benefits for the unit of their labor activities with the maidservants, that is to say with their family life that would be directly favored and that indirectly it would benefit the employer since its worker's yield would increase encouraged by the presence of its family nucleus. From the juridical optics the appropriate regulation of the telework in the Ecuador is very necessary, since this work form at distance is perfectly applicable so that people with physical disability can make a work and to exercise its constitutional right to the work and the Good Living that it proclaims the Constitution of the Republic of the Ecuador.